Speech acts in the massively multiplayer game Tibia - Azevedo, Paula Marilu Raymundo (Revista da Graduação, 2010)
This paper aims at verifying the most common speech acts present in the massively multiplayer role-playing game Tibia. In such game, players from all around the world take the roles of characters and lead a virtual life, which includes social and communicative interactions. The interactions carried out by player characters are analyzed in the light of the speech act theory. That is, this study presents an analysis of the structure and content of the messages players attempt to convey within their dialogues in the game. Finally, as English is the standard language used in Tibia, it is believed that the game can be beneficial for learners of English as a foreign language.